Some Aspects of Reproductive Biology of European Pilchard, Sardina Pilchardus in Derna Coast, Eastern Libya (Libyan Journal of Ecological & Environmental Sciences and Technology, 2020)
The reproductive biology of 700 specimens of Sardina pilchardus were collected monthly from the catch of trawling net and lampara fishery operating on the Derna coast on the Mediterranean Sea from August (2017) to July (2018). There were monthly variations in sex ratio between males (280 fish = 40.0 %( and females (420 fish = 60.0%). The overall sex ratio was 1: 1.50 in favor of females. The breeding season extended from October to May with a peak in November till February. The length at first maturity was L50 for males 14.5cm and L50 for females 15.5cm. The average absolute fecundity ranged from 11467±4097 to 90463±10123. Overall average absolute fecundity was 47989±7994, whereas overall relative fecundity was 2551±349/cm for total length ranging from 10.5 to 24.4cm.
Keywords: Reproductive biology; Sardina pilchardus; eastern coast; Mediterranean Sea; Derna; Libya